Condition of the ability and capability in (Al-Ihtisab) the Promotion of Virtue and Prevention of Vice its evidence and regulations - Hawsawi, Asma Adam (Journal of Islamic Sciences, 2022)
The objective of the research is to root the condition of ability and capability to (Al-Ihtisab) the Promotion of Virtue and Prevention of Vice, extract the Islamic legal concept of it, and explain how to apply it into reality. The inductive method has been used in most of the research in collecting its material, and the deductive method to produce the Islamic legal rules related to it. The results concluded that the intent of the condition of the ability and capability is a presumption that outweighs the interest of Islamic law, and the presence of sensory and moral preparation for the responsible which enables him to influence in Prevention of Vice, and the encouragement of wise Sharia in the Promotion of Virtue and Prevention of Vice and reform from everyone, each according to his ability and capability.